2020
DOI: 10.1007/s11606-020-05896-x
|View full text |Cite
|
Sign up to set email alerts
|

Online Crowdfunding Response to Coronavirus Disease 2019

Abstract: We designed and implemented a custom web scraping tool to extract campaign data on GoFundMe.com. The software was constructed in a Python environment using the Selenium (www.selenium.dev) software testing framework and Scrapy (www.scrapy.org) open-source framework in tandem to navigate the website architecture. We extracted data for active campaigns using the keywords relevant to COVID-19 pandemic and characterized campaigns that emerged March 3-20, 2020, the period which coincided with an inflection point in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 4 publications
2
25
0
Order By: Relevance
“…This shows the reactionary crowdfunding response of Canadians as it became clear that COVID-19 was to become a serious societal crisis, and how digital donation-based crowdfunding acted as a primary medium for Canadians to manage the crisis, whether by donating, or by campaigning for themselves or on behalf of others. Similar trends were seen in American crowdfunding, where creation of COVID-19 related campaigns coincided temporally with increases in detected COVID-19 cases [ 20 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This shows the reactionary crowdfunding response of Canadians as it became clear that COVID-19 was to become a serious societal crisis, and how digital donation-based crowdfunding acted as a primary medium for Canadians to manage the crisis, whether by donating, or by campaigning for themselves or on behalf of others. Similar trends were seen in American crowdfunding, where creation of COVID-19 related campaigns coincided temporally with increases in detected COVID-19 cases [ 20 ].…”
Section: Discussionsupporting
confidence: 67%
“…This method of data collection has previously been used to target and gather campaigns raising money for a specific purpose, which are then quantitatively analyzed to examine the qualities of these campaigns. For example, Duynhoven et al used scraped campaigns to analyze the spatial trends in Canadian crowdfunding campaigns for cancer [ 15 ], and more recently scraped campaigns have been used to examine the quantitative trends of crowdfunding for COVID-19 at large [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the initial peak of the pandemic, there was a global shortage of PPE. In a recent study evaluating crowdfunding during the initial phase of the COVID-19 pandemic, most of the European campaigns were fundraising for hospitals and medical supplies, as there were severe shortages of PPE and other medical equipment [ 15 ]. Two months after the outbreak in Poland, more than 1 in 5 responders still indicated that their main worksite did not provide sufficient PPE.…”
Section: Discussionmentioning
confidence: 99%
“…It seems reasonable that this scenario could have induced a general discontent, which, in turn, may affect the tendency to help each other. To deal with the consequences of COVID‐19, an increasing number of fundraisings were created (Rajwa et al, 2020 ). Thus, in the unusual circumstances of the pandemic, it is meaningful to understand if societal discontent can influence the willingness to help others, particularly those who suffer physically and/or economically from coronavirus.…”
Section: The Present Researchmentioning
confidence: 99%